Legal and Technical Aspects of Web Forensics - Sonmez, Yesim Ulgen; Varol, Asaf (Ieee, 2019)
Web forensics is a discipline that has legal and technical aspects and deals with a continuously expanding problem. This study has been conducted for two reasons-to answer the question 'Can criminal tendency be detected from web activities?' and to contribute to technical developments in computer forensics. Criminal records for conventional and cybercrimes committed in Turkey, detection of criminals, the sentences given, and the methods used have been examined. The technical developments in the literature dealing with web forensics have been investigated and emphasis has been laid on the types of crimes to be handled in order to develop new models. The process, method, technique, application and software of the web forensics procedure, which handles web activities, have been investigated. We observed that problems are encountered mainly at the stage of evidence analysis. The crime models that were analyzed in the legal department were determined in order to create a database for new models in the technical field.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: web forensics; information technology law